Saunders comprehensive review for NCLEX-PN - Silvestri, Linda Anne (Saunders, 2003)
Salve Regina Univ., Charlestown, RI. Brandon/Hill Nursing List selection (#306). Review tool for the NCLEX-PN. Offers a review of each aspect of practical nursing, chapter on medications and dosages, and more than 1,500 practice questions. Previous edition: c2000. Softcover.